PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KIRNERJA KARYAWAN PT. ANTAM (Persero) Tbk. UNIT BISNIS PERTAMBANGAN NIKEL (UBPN) KOLAKA - Muhammad Basri; Rosfiah Arsal; Hasran (Halu Oleo University, 2024)
This study aims to examine the influence of the work environment and work motivation on the performance of employees of PT. Antam Tbk. UBPN Kolaka, The type of data is quantitative data sourced from 108 employee respondents using a questionnaire instrument in the form of a Google form as a data collection technique. The sampling technique is random sampling. The data were processed using statistical tests and analyzed by multiple regression. The results of the study show that, partially, the work environment does not have a significant effect on employee performance, but it needs to be explained that, in general, the employees surveyed are those who work in open spaces (not in offices/buildings), on the contrary, work motivation has a significant effect on employee performance. Simultaneously showed a significant influence between the driving environment and work motivation on employee performance.